Fear of Cancer Recurrence and Coping among Breast Cancer Survivors among Indian Females: A Longitudinal Study - Thakur, Monika; Mishra, Anand Kumar; Lata, Kusum; N., Jagadeesha H.; Kaur, Simrat (Indian Journal of Medical and Paediatric Oncology, 2025)
Breast cancer survivors (BCSs) may experience a cascade of negative reactions during the entire treatment process. Post-treatment, the most common challenge among all fears is cancer recurrence. The fear brings many forms of psychological morbidity during follow-up. However, coping throughout and beyond cancer helps survivors hold a strong pillar of support as part of backup.This study aims to assess the interplay of the fear of cancer recurrence (FCR) and how it impacts the distress and relation of coping with recurrence.A longitudinal study was conducted in a tertiary care center in North India: T1 (January 2021–April 2021) and T2 (May 2023–September 2023). A total of 700 BCSs were approached initially, and after 2 years, they were again screened using the purposive sampling technique. Statistical Package for Social Sciences (SPSS) 23 was used to analyze the data.The patients' mean age ( standard deviation [SD]) was 48.14 (8.53) years. The mean (SD) FCR score was 15.26 (4.45). There was an inverse association between the FCR score and the coping score. The higher the age, the lesser the FCR score and the better religious coping.Psychological FCR is a detachable part of patients' worry once a person is diagnosed with any threatening illness. The coping mechanism should be strengthened by providing psychosocial interventions, family therapy, and other individual-centered therapies.
Keywords: breast cancer survivor; fear of cancer recurrence; coping; psychological distress; depression; women; India